Bioleaching of a Chalcocite-Dominant Copper Ore from Salta, Argentina, by Mesophilic and Thermophilic Microorganisms - Amar, Agustina (2023)
The study and development of new sustainable mining methods to exploit low-grade ores and secondary metallic resources are essential to meet global demand and contribute to caring for the environment. Copper is one of the most widely used metals and chalcocite is the main secondary sulfide of this metal. Therefore, the study of copper recovery from chalcocite-dominant minerals could have a great impact on the industry. In this study, we assess at bench scale the feasibility of applying biohydrometallurgical processes to extract copper from chalcocite-rich minerals from Taca Taca, Argentina, using native mesophilic microorganisms (30 °C) and thermophiles (45, 65 °C). The indigenous mesophilic consortium was dominated by Acidithiobacillus ferrooxidans and could solubilize all the copper present in the systems (113 mg/L) within three weeks without any change in the pH of the solution. Notably, by increasing the temperature up to 45 and 65 °C, copper leaching was enhanced, completing the recovery in 7–14 days. The oxidizing microorganisms active in these conditions were Ferroplasma sp. and Acidianus copahuensis, respectively. An increase in the abiotic copper recovery was also observed as temperature rose; as well as a slight acidification of the solution. This study constitutes the first assessment for the bioleaching of Taca Taca ores.